1990
DOI: 10.1038/345686a0
|View full text |Cite
|
Sign up to set email alerts
|

A POU-domain transcription factor in early stem cells and germ cells of the mammalian embryo

Abstract: The murine oct-3 gene encodes a transcription factor containing a POU-specific domain and a homeodomain. In marked contrast to other homeodomain-encoding genes, oct-3 is expressed in the totipotent and pluripotent stem cells of the pregastrulation embryo and is down-regulated during differentiation to endoderm and mesoderm, suggesting that it has a role in early development. The oct-3 gene is also expressed in primordial germ cells and in the female germ line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
641
1
10

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 866 publications
(676 citation statements)
references
References 41 publications
22
641
1
10
Order By: Relevance
“…Of interest, it has recently been shown that Trh may be a direct transcriptional target of POU5F1, a well-characterized marker of pluripotency in embryonic stem cells and the epiblast (Loh et al, 2006;Matoba et al, 2006). Pou5f1 expression in the epiblast overlaps with that of Trh, suggesting that POU5F1 may in part be regulating Trh expression at this stage (Rosner et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, it has recently been shown that Trh may be a direct transcriptional target of POU5F1, a well-characterized marker of pluripotency in embryonic stem cells and the epiblast (Loh et al, 2006;Matoba et al, 2006). Pou5f1 expression in the epiblast overlaps with that of Trh, suggesting that POU5F1 may in part be regulating Trh expression at this stage (Rosner et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…20,[24][25][26] During this time, the pluripotency-associated genes Oct4, Sox2, and Nanog are progressively restricted to the germline and become germ cell specific at E8.0. [27][28][29] The means by which a limited subset of cells is initially selected from among the larger number of competent cells in the correct position of the posterior epiblast is unclear.…”
Section: Specification Of the Germlinementioning
confidence: 99%
“…31 Likewise, Oct4 is required to form Dppa3-expressing PGCs but is expressed in cells outside the putative germ cell lineage at the time of specification. 29,32 Despite the division between preformation and induction, fundamental similarities exist in the germ cell specification of worm, fly, and mouse. Each species sets aside a dedicated set of germ cell precursors -P 4 35 A maternally-inherited P granule protein, PIE-1, is required for this transcriptional silencing: in embryos derived from pie-1 mutants, zygotic transcripts are aberrantly present in the embryonic germ cell precursors, and the germline does not develop.…”
Section: Specification Of the Germlinementioning
confidence: 99%
“…Specific expression of Oct 3/4 has been related to the pluripotent capacity of testicular GCTs, suggesting their origin from transformed pluripotent progenitor cells, such as PGCs [100]. Oct 3/4 is critical for the self-renewal of ES cells [124] and, under physiological conditions, Oct 3/4 transcription factor is expressed exclusively in pluripotent ES cells, PGCs, oogonia, and gonocytes [60,65,147] and its expression is downregulated during differentiation [138]. Many similarities exist between testicular and ovarian GCTs, including morphological resemblance and a similar pattern of chromosomal alterations [143].…”
Section: Ovarian Cancer: Pluripotency and Putative Cscsmentioning
confidence: 99%